PERANAN KHADIJAH TERHADAP PENYEBARAN AGAMA ISLAM DI MEKAH - Iqbal, Iqbal (Rihlah: Jurnal Sejarah dan Kebudayaan, 2017)
Khadijah is the first women became a moslem. She is Prophet Muhammad’s wife. Before she became a moslem, she is a rich women. She has high status in Quraisy clan. When prophet Muhammad invited everyone in Quraisy clan to be moslem, She was care and protected Prophet Muhammad from Quraisy clan. She merried with Muhammad when fourty years old and Muhammad is twenty five years old. She met with him when Prophet Muhammad became a worker in her bussiness. After Muhammad sold in Syam, she interested to Muhammad. Finally, She said to Nufaisah about her love to Muhammad. Nufaisah is her friend. Nufaisah came to Muhammad and talked about Khadijah’s love. So, after Muhammad had agreed, they merried. They had three boys and four daughter. They are al-Qasim, al-Thayyib dan al-Thahir, Ruqayyah, Zainab, Ummu Kultsum and Fathimah. She died when sixty five years old.